Knowledge portal for handicraft products (KM) - Lai Ching, Wong (2012)
Knowledge is important in life.It is include experience and data in term of vary types of media format.Knowledge Management System is used to create,store,share and use knowledge for right people at the correct time.Handicraft is the spirit of cultural.Knowledge Portal for Handicraft Products is a single access point to the handicraft knowledge.The methodology model that used in developing this portal is iterative and incremental model.Review existing system and interview session was conducted to collect data regarding to the handicraft products.Functional testing is used to test the functional of the portal is fulfil user requirements.This portal is managed by Jabatan Pertanian Negeri Pahang.Handicraft expert may give advices. Handicraft businessman can promote their product and registered user also can comment at the forum.It can help to solve lack of communication platform within users.Interview with the businessman and expert is conducted to collect the knowledge and experiences from them.Review of the existing system is help to identify the current issues of the existing system and technology using recently Knowledge Portal for Handicraft Products is expected to increase the productivity of handicraft products in Pahang state and Malaysia.It is also help to identify handicraft experts to share knowledge with users.Motivation of users in sharing knowledge is important to achieve the objectives of this knowledge portal.